Variabilidade espacial de atributos de solos coesos do leste maranhense - Resende, José Maria Do Amaral; Marques Júnior, José [UNESP]; Martins Filho, Marcilio Vieira [UNESP]; Dantas, Jussara Silva; Siqueira, Diego Silva; Teixeira, Daniel De Bortoli [UNESP] (Sociedade Brasileira de Ciência do Solo, 2014)
The national and international demand for maps of soil properties has increased. The aim of this study was to characterize cohesive soils and associate their variability of particle size, chemical properties, and color to different landforms in agricultural areas and native vegetation using geostatistical techniques. To set up the experiment, we selected three areas of soil consisting of an area planted to soybeans and, contiguous to it, another area with plant cover remaining from three types of cerrado (tropical savanna), designated Cerradão (A), Cerrado (B), and Campo Cerrado (C). The areas A and B are located on a concave landform, while area C is on a convex landform. Sampling grids with 121 points were established in each area, and in areas with native vegetation, transects were constructed with five points spaced at 20 m. The largest mean ranges, considering both depths evaluated, were found for area A, with 115 m for particle size, 157 m for chemical attributes, and 168 m for soil color. Area B had mean ranges of 95, 64, and 160 m for grain size, chemical attribute, and soil color, respectively. For its part, area C exhibited the mean ranges of 63, 65, and 58 m in grain size, chemical attributes, and soil color, respectively. The environment with the greatest variability (area C) is related to locations with the occurrence of Campo Cerrado vegetation and a convex landform. This same site had the lowest responsiveness to soybean crop management, shown by soil fertility indicators for this crop, especially the low values for organic matter (9.20 mg kg-1) and CEC (29.60 mmol c dm-3). Thus, it can be stated that for the geological compartment studied, the environments of high variability will always be associated with areas with lower response to soil management for soybean.

A demanda nacional e internacional por mapas de atributos do solo tem aumentado. Os objetivos deste trabalho foram caracterizar e associar a variabilidade da granulometria, os atributos químicos e a cor de solos coesos a diferentes formas de paisagem, em áreas agrícolas e de vegetação nativa, por meio de técnicas geoestatísticas. Para a instalação do experimento, foram escolhidas três áreas representadas por uma área cultivada com soja e, contígua a essa, uma com cobertura vegetal remanescente de três feições de cerrado, designadas de Cerradão (A), Cerrado (B) e Campo Cerrado (C). As áreas A e B estão localizadas em pedoforma côncava e a área C, na convexa. Em cada área, foram estabelecidas malhas de amostragem com 121 pontos; nas áreas com cobertura vegetal construíram-se transeções com cinco pontos espaçados em 20 m. Os maiores alcances médios, considerando ambas as profundidades avaliadas, foram encontrados para a área A, sendo de 115 m para granulometria, 157 m para atributos químicos e 168 m para a cor do solo. A área B apresentou alcances médios de 95, 64 e 160 m para granulometria, atributos químicos e cor do solo, respectivamente. A área C, por sua vez, exibiu alcances médios de 63, 65 e 58 m para granulometria, atributos químicos e cor do solo, respectivamente. O ambiente com maior variabilidade (área C) está relacionado com locais de ocorrência de vegetação do tipo Campo Cerrado e pedoforma convexa. Esse mesmo local evidenciou a menor capacidade de resposta ao manejo da cultura de soja, evidenciado pelos índices de fertilidade do solo para essa cultura, com destaque para os baixos valores de matéria orgânica (9,20 mg kg-1) e CTC (29,60 mmol c dm-3). Assim, pode-se afirmar que para o compartimento geológico estudado, os ambientes de alta variabilidade sempre estão associados a áreas com menor resposta ao manejo do solo para a cultura da soja.
Spatial variability of the properties of cohesive soils from eastern Maranhão, Brazil
Keywords: geoestatística; espectroscopia de reflectância difusa; cerrado; geostatistics; diffuse reflectance spectroscopy; savanna